D3.js 4.x data visualization : learn to visualize your data with JavaScript - Rininsland, AEndrew; Teller, Swizec (Packt Publishing, 2017)
Create and publish your own interactive and compelling data visualizations with D3.js 4.x About This Book Build interactive and rich graphics and visualization using JavaScript`s powerful library D3.js Learn D3 from the ground up, using the all-new version 4 of the library Gain insight into producing high-quality, extensible charts and visualizations using best practices such as writing testable, extensible code and strong typing Who This Book Is For This book is for web developers, interactive news developers, data scientists, and anyone interested in representing data through interactive visualizations on the Web with D3. Some basic knowledge of JavaScript is expected, but no prior experience with data visualization or D3 is required to follow this book. What You Will Learn Map data to visual elements using D3's scales Draw SVG elements using D3's shape generators Transform data using D3's collection methods Use D3's various layout patterns to quickly generate various common types of chart Write modern JavaScript using ES2017 and Babel Explore the basics of unit testing D3 visualizations using Mocha and Chai Write and deploy a simple Node.js web service to render charts via HTML Canvas Understand what makes a good data visualization and how to use the tools at your disposal to create accurate charts In Detail Want to get started with impressive interactive visualizations and implement them in your daily tasks? This book offers the perfect solution-D3.js. It has emerged as the most popular tool for data visualization. This book will teach you how to implement the features of the latest version of D3 while writing JavaScript using the newest tools and technique You will start by setting up the D3 environment and making your first basic bar chart. You will then build stunning SVG and Canvas-based data visualizations while writing testable, extensible code,as accurate and informative as it is visually stimulating. Step-by-step examples walk you through creating, integrating, and debugging different types of visualization and will have you building basic visualizations (such as bar, line, and scatter graphs) in no time. By the end of this book, you will have mastered the techniques necessary to successfully visualize data and will be ready to use D3 to transform any data into an engaging and sophisticated visualization. Style and approach This book follows a tutorial-based approach in teaching the world's most powerful data visualization library,...